754 Non-conducted premature atrial complexes: a new predictor for atrial fibrillation in cryptogenic stroke patients. (8th December 2021) - Vetta, Giampaolo; Parlavecchio, Antonio; Caminiti, Rodolfo; Magnocavallo, Michele; Lavalle, Carlo; Della Rocca, Domenico G; Marano, Giovanni; Ruggieri, Chiara; Crea, Pasquale; Dattilo, Giuseppe; Ferrau, Ludovica; Musolino, Rosa; et al.
Abstract: Aims: Atrial fibrillation (AF) is the main cardiac cause of stroke, but it frequently remains undetected. In these patient monitoring for AF is recommended using a Holter electrocardiogram (ECG). The aim of the present study is to study non-conducted atrial complexes (ncPAC) recorded on Holter ECG as a new predictor of AF. Methods and results: Patients admitted to the Stroke Unit of our hospital for cryptogenic stroke from December 2018 to January 2020 who underwent 24-h electrocardiographic monitoring were prospectively enrolled in the study and were subsequently submitted to 3-month and 6-month follow-up to investigate the occurrence of AF. The study recruited 112 patients. At follow-up visit, AF was diagnosed in 21.4% of the population. The only statistically significant difference between the group with and without a AF diagnosis was the presence of ncPAC (83.3% vs. 16.7%; P  < 0.0001). ROC analysis was performed and showed that ncPAC had the best diagnostic accuracy in the AF diagnosis [AUC: 0.798; confidence interval (CI): 0.675–0.921]. The AUC of ncPAC was significantly better than the AUC of premature atrial complexes (PACs) ( P  < 0.05), CHA2 DS2 -VASc, HATCH, HAVOC, and C2 HEST scores ( P  < 0.01). Kaplan–Meier curve survival estimate for AF onset by the presence of ncPAC revealed that there was a significant difference in the AF onset between patients with ncPAC and those without ( P  < 0.0001) and multivariate Cox-proportional hazard analysis revealed that ncPAC presence was an independent predictors of AF onset [hazards ratio (HR): 9.28; CI 95%: 2, 66–32, 40; P  = 0.0001]. Conclusions: The presence of ncPAC represents a new predictor of AF that could further guide the investigation of AF in patients with cryptogenic stroke.